Increased Tissue Conductance and Ion Transport in Guinea Pig Ileum After Exposure to Staphylococcus aureus Delta-Toxin In Vitro - O'Brien, Alison D. (1978)
Prior studies had shown that Staphylococcus aureus delta-toxin was able to inhibit water absorption in guinea pig ileum and to elevate the cyclic AMP content of this tissue, but was unable to elicit certain cyclic AMP-mediated changes in Y-1 adrenal or Chinese hamster ovary cells. Because water movement passively follows the net movement of electrolytes in the gut, this study investigated the effect of delta-toxin on ion transport in guinea pig ileum maintained in vitro. The transmural potential difference (PD) of guinea pig ileum was measured and nullified with an automatic voltage clamp. The short circuit flowing under these conditions (I(sc)) was measured, and the conductance was calculated (I(sc)/PD). Unidirectional (22)Na(+) and (36)Cl(−) fluxes were measured. In a glucose-free Ringer solution, delta-toxin caused an immediate spike in PD and I(sc), and the extent and duration of the spike generally increased with increasing toxin concentration. The conductance of ileum was increased by delta-toxin, and this effect on conductance could be blocked by lecithin, a known inhibitor of delta-toxin. Tissue in the presence of glucose did not exhibit a spike in PD or I(sc) when exposed to delta-toxin. In a glucose-free medium, delta-toxin caused a 1.5- to 2.5-fold increase in both the unidirectional absorption and secretion of Na(+) and Cl(−), whereas the net secretion of Na(+) increased above basal levels. The observation that delta-toxin causes a prompt increase in intestinal ion flux lends credence to the concept that the elevation in cellular cyclic AMP, which occurs later, is a secondary response to the toxin. The rapid increase in ion flux may reflect the ability of delta-toxin to augment intercellular movement of ions across the mucosa rather than the stimulation of transcellular processes.